Comparison of scalar and vector electrocardiographic diagnosis and localization of myocardial infarction. - McNeill, G (Br Heart J, 1975)
A prospective study was made of 80 patients during typical clinical episodes of acute myocardial infarction with biochemical and scalar electrocardiographic confirmation. Nine patients had bundle-branch block and 12 had had previous episodes of myocardial infarction. Serial electrocardiograms and vectorcardiograms were recorded during the first week in hospital. The most striking finding was that in more than half the cases there was disagreement between the electrocardiogram and vectorcardiogram in the localizationof infarction. The earliest evidence of infarction in the electrocardiogram is often restricted to ST and T changes though in the corresponding vectorcardiograms evidence of infarction may be present in the QRS loop. In those cases in which both electrocardiogram and vectorcardiogram show QRS abnormalities these are frequently detected earlier in the vectorcardiogram, but the converse is rare.